Oral fexinidazole for stage 1 or early stage 2 African Trypanosoma brucei gambiense trypanosomiasis: a prospective, multicentre, open-label, cohort study. Issue 7 (July 2021) - Kande Betu Ku Mesu, Victor; Mutombo Kalonji, Wilfried; Bardonneau, Clélia; Valverde Mordt, Olaf; Ngolo Tete, Digas; Blesson, Séverine; Simon, François; Delhomme, Sophie; Bernhard, Sonja; Mahenzi Mbembo, Hélène; Mpia Moke, Christian; Lumeya Vuvu, Steven; et al.
Summary: Background: Staging and treatment of human African trypanosomiasis caused by Trypanosoma brucei gambiense (g-HAT) required lumbar puncture to assess cerebrospinal fluid (CSF) and intravenous drugs that cross the blood–brain barrier for late-stage infection. These procedures are inconvenient in rural health systems of disease-endemic countries. A pivotal study established fexinidazole as the first oral monotherapy to be effective against non-severe stage 2 g-HAT. We aimed to assess the safety and efficacy of fexinidazole in early g-HAT. Methods: In this prospective, multicentre, open-label, single-arm cohort study, patients with stage 1 or early stage 2 g-HAT were recruited from eight treatment centres in the Democratic Republic of the Congo. Primary inclusion criteria included being older than 15 years, being able to ingest at least one complete meal per day (or at least one sachet of Plumpy'Nut®), a Karnofsky score higher than 50, evidence of trypanosomes in the blood or lymph but no evidence of trypanosomes in the CSF, willingness to be admitted to hospital to receive treatment, having a permanent address, and being able to comply with the follow-up visit schedule. Exclusion criteria included severe malnutrition, inability to take medication orally, pregnant or breastfeeding women, any clinically important medical condition that could jeopardise patient safety or participation in the study, severely deteriorated general status, any contraindication to imidazole drugs, HAT treatment in the past 2 years, previous enrolment in the study or previous intake of fexinidazole, abnormalities on electrocardiogram that did not return to normal in pretreatment repeated assessments or were considered clinically important, QT interval corrected using Fridericia's formula of at least 450 ms, and patients not tested for malaria or not having received appropriate treatment for malaria or for soil-transmitted helminthiasis. Patients were classified into stage 1 or early stage 2 g-HAT groups following evidence of trypanosomes in the blood, lymph, and absence in CSF, and using white-blood-cell count in CSF. Patients received 1800 mg fexinidazole once per day on days 1–4 then 1200 mg fexinidazole on days 5–10. Patients were observed for approximately 19 months in total. Study participants were followed up on day 5 and day 8 during treatment, at end of treatment on day 11, at end of hospitalisation on days 11–18, at week 9 for a subset of patients, and after 6 months, 12 months, and 18 months. The primary endpoint was treatment success at 12 months. Safety was assessed through routine monitoring. Analyses were done in the intention-to-treat population. The acceptable success rate was defined as treatment efficacy in more than 80% of patients. This study is completed and registered with ClinicalTrials.gov (NCT02169557 ). Findings: Patients were enrolled between April 30, 2014, and April 25, 2017. 238 patients were recruited: 195 (82%) patients with stage 1 g-HAT and 43 (18%) with early stage 2 g-HAT. 189 (97%) of 195 patients with stage 1 g-HAT and 41 (95%) of 43 patients with early stage 2 g-HAT were finally included and completed the 10 day treatment period. Three patients with stage 1 g-HAT died after the 10 day treatment period and before the 12 month primary follow-up visit, considered as treatment failure and were withdrawn from the study. Treatment was effective at 12 months for 227 (99%) of 230 patients (95% CI 96·2–99·7): 186 (98%) of 189 patients (95·4–99·7) with stage 1 and 41 (100%) of 41 patients (91·4–100·0) with early stage 2, indicating that the primary study endpoint was met. No new safety issues were observed. The most frequent adverse events were headache and vomiting. In total, 214 (93%) of 230 patients had treatment-emergent adverse events, mainly common-terminology criteria for adverse events grades 1 to 3. None led to treatment discontinuation. Interpretation: Fexinidazole is a valuable first-line treatment option in the early stages of g-HAT. Funding: Through the Drugs for Neglected Diseases initiative : the Bill & Melinda Gates Foundation, the Republic and Canton of Geneva (Switzerland), the Dutch Ministry of Foreign Affairs (also known as DGIS; Netherlands), the Norwegian Agency for Development Cooperation (also known as Norad; Norway), the Federal Ministry of Education and Research (also known as BMBF) through KfW (Germany), the Brian Mercer Charitable Trust (UK), and other private foundations and individuals from the HAT campaign. Translation: For the French translation of the abstract see Supplementary Materials section.